SAT0506 Towards the Development of an Ultrasound Composite Disease Activity Score for Juvenile Idiopathic Arthritis. (9th June 2015) - Borzani, I.; Di Landro, G.; Ravelli, A.; Corona, F.; Filocamo, G.
Abstract : Background: Assessment of disease activity is a fundamental component of the clinical evaluation of children with Juvenile Idiopathic Arthritis (JIA) and the first composite disease activity score for JIA, the Juvenile Arthritis Disease Activity Score (JADAS), was reported.[1] Ultrasound (US) is a powerful tool for the assessment of joint disease and has been shown to be more accurate than clinical examination in detecting synovitis. However, the validity of Gray Scale US (GSUS) and Power Doppler US (PDUS) techniques for evaluating inflammatory activity in affected joints needs to be defined. Objectives: To develop and to investigate the construct validity of a composite disease activity index for JIA that includes US findings of synovitis compared with cJADAS in assessing joint inflammation. Methods: Before the study visit, parents of children with JIA were asked to complete the Juvenile Arthritis Multidimensional Assessment Report (JAMAR), which includes a standardized assessment of pain and WB on a 21-numbered circle visual analog scales (VAS), and several other parent centered JIA outcome measures. At study visit, a pediatric rheumatologist, who was unaware of parent's reports, performed a formal joint assessment and scored the physician's global assessment (PG) on 21-numbered circle VAS. After the visit, a pediatric radiologist with almost 10 years of experience in US assessment in JIA, evaluated independently the presence or the absence of synovial hypertrophy/effusion (GSUS), and PDUS in elbows, wrists, metacarpophalangeal and interphalangeal joints, knees and ankles. The joints with hypertrophy/effusion at GSUS and positivity for PDUS was defined GSUS and PDUS active joints respectively. In each patient, the GSUS and the PDUS JADAS -10 were calculated as the sum of the scores of GSUS active joints and PDUS active joints to a maximum of 10 respectively, the parent WB, and the PG, which yields a global score between 0 to 30. The correlation between the number of active joints defined clinically, GSUS and PDUS active joints, the GSUS and PDUS JADAS-10 and the clinical JADAS-10 (2) was assessed using Spearman's rank correlation. Correlations were considered high if 0.7, moderate if 0.4–0.7, and low if <0.4. Results: The JAMAR was completed by parents of 28 unselected patients, 17 with persistent oligoarthritis, 4 with extended oligoarthritis, 6 with rheumatoid factor-negative polyarthritis, 1 with systemic arthritis; aged between 5 months and 21 years. The median (range) of cJADAS-10 (2) was 12.25 (0-26.5). The table shows the correlation between the the active joint count and the cJADAS 10 with the variables considered. Conclusions: The preliminary results of the construct validity of a composite disease activity score for JIA that encompasses ultrasound findings of synovitis, evidenced high correlation between the clinical JADAS 10 and US JADAS 10, both for GSUS and PDUS. The correlation between the active joint count defined clinically with the active joints evidenced by US was moderate. References: Consolaro A et al. Development and validation of a composite disease activity score for juvenile idiopathic arthritis. Arthritis Rheum. 2009 Consolaro A, et al. Arthritis Care Res 2014 Disclosure of Interest: None declared